Association between pain, anxiety, and alpha2 frontal activity in women with fibromyalgia - Géssika Araújo de Melo; Marcela Lais Lima Holmes Madruga; Cleudyson Joab de Araújo Silva; Nelson Torro (Acta Scientiarum. Health Sciences, 2021)
Fibromyalgia is a disorder of the central nervous system, with the presence of chronic generalized pain, fatigue, morning stiffness, anxiety and depression symptoms. Higher amplitudes of the frequency band alpha2 have been associated with higher relaxation in this population. In the present study, we analysed the association between pain, anxiety, and the spectral power of alpha2 frontal in women with fibromyalgia. Thirty-one women diagnosed with fibromyalgia, for at least three months, took part in the study. Results revealed a statistically significant positive relationship between pain and anxiety levels. However, we found no association between the spectral power of alpha2 in the frontal cortex and the measures between anxiety and pain in the patients. Present findings emphasize the importance of understanding the cortical activity and the central control mechanisms in fibromyalgia.